The Mediating Roles of Psychological Autonomy, Competence and Relatedness on Work-Life Balance and Well-Being - Fotiadis, Anestis; Abdulrahman, Khadija; Spyridou, Anastasia (Frontiers in Psychology, 2019)
The main objective of this current research is to investigate the impact of “work balance” on “psychological well-being” using employees within the hospitality industry in UAE as statistical units. To meet the objective of this research, we developed a structural equation model to examine how psychological autonomy, psychological competence, and psychological relatedness affect psychological well-being and work-life balance, as well as the effect of work-life balance on psychological well-being. We also examine the mediating effect of work-life balance in these relationships. The results of this study show that psychological autonomy affect positively both psychological well-being and work-life balance, whereas psychological competence only affect psychological well-being positive. Moreover, psychological relatedness affects negatively both psychological well-being and work-life balance while work-life balance affects positively psychological well-being.